Brooke-Spiegler Syndrome: A Rare Entity - Monika Rathi; Seema Awasthi; Satish Kumar Budania; Faiyaz Ahmad; Shyamoli Dutta; Ashutosh Kumar (Case Reports in Pathology)
Brooke-Spiegler syndrome is a rare entity. It is an autosomal dominant syndrome in which multiple trichoepitheliomas, cylindromas, or other adnexal tumors are seen. Very few cases of Brooke-Spiegler syndrome are reported in the literature. We came across a 40 -year-old female in which multiple trichoepitheliomas and cylindromas were seen on scalp. In view of clinical history and histopathological examination it was diagnosed as Brooke-Spiegler syndrome. We report this case because of its rarity.